Endocrine-dependent expression of circadian clock genes in insects - Doležel, David; Zdechovanová, Lenka; Šauman, Ivo; Hodková, Magdalena (Cellular and molecular life sciences, 2008)
Current models state that insect peripheral oscillators are directly responsive to light, while mammalian peripheral clock genes are coordinated by a master clock in the brain via intermediate factors, possibly hormonal. We show that the expression levels of two circadian clock genes, period (per) and Par Domain Protein 1 (Pdp1) in the peripheral tissue of an insect model species, the linden bug Pyrrhocoris apterus, are inversely affected by contrasting photoperiods. The effect of photoperiod on per and Pdp1 mRNA levels was found to be mediated by the corpus allatum, an endocrine gland producing juvenile hormone. Our results provide the first experimental evidence for the effect of an endocrine gland on circadian clock gene expression in insects.
Keywords: Gene Expression Regulation; CLOCK Proteins; transkripční faktory bZIP; jaderné proteiny; Basic-Leucine Zipper Transcription Factors; cirkadiánní rytmus; Endocrine System; endokrinní systém; Circadian Rhythm; trans-aktivátory; Animals; ženské pohlaví; Period Circadian Proteins; zvířata; regulace genové exprese; Financing, Organized; Trans-Activators; Female; financování organizované; Nuclear Proteins; Heteroptera